Multi-damage accelerated life test based on the Birnbaum-Saunders reliability evaluation model - Chenggong Lu; Zhiqiang Wei; Hongxia Qiao; Theogene Hakuzweyezu; Guobin Qiao; Kan Li; Bingrong Zhu (Journal of Asian Architecture and Building Engineering, 2023)
The present study aims to reveal the deterioration law and service life of concrete durability in the saline soil area of western China. For this purpose, the indoor accelerated tests with multiple damage factors including compound salt erosion, dry-wet cycle, freeze-thaw damage, and solar radiation were designed. The deterioration mechanisms of concrete durability were analysed from both macroscopic and microscopic aspects. The Birnbaum-Saunders (B-S) model was selected for modeling, and parameters were estimated by various methods such as moment estimation method (MEM), inverse estimation method (IMEM), quantile estimation Method (QEM), regression estimation method (REM), and maximum likelihood method (MIM). The results showed that under the action of multiple damage factors, the surface of the concrete gradually becomes rough and pitted from the initial smooth and flat surface. As the concrete’s interior gel is not dense, rod-shaped, and needle-shaped corrosion products were formed. For the two-parameter model, the reliability curve, density curve, and failure rate curve obtained by the QEM differ the most from the other 5 types of parameter estimation methods. When the MEM is used for parameter estimation, the difference between the two-parameter model and the three-parameter model under the same reliability level is relatively small.